Pressurized Hot Water Extraction of Mangosteen Pericarp and Its Associated Molecular Signatures in Endothelial Cells - Sakeena Si Yu Tan; Meyammai Shanmugham; Yu Ling Chin; Jia An; Chee Kai Chua; Eng Shi Ong; Chen Huei Leo (MDPI AG, 2023)
The mangosteen (Garcinia mangostana L.) pericarp is known to be rich in potent bioactive phytochemical compounds such as xanthones, which possess pharmacologically important antioxidant activity and beneficial cardiometabolic properties. Mangosteen pericarp is typically classified as unavoidable food waste and discarded, despite being rich in bioactive phytochemical compounds that therefore present an exciting opportunity for valorization. Thus, this study aims to extract phytochemical compounds from mangosteen pericarp using pressurized hot water extraction (PHWE) and determine its biological effects in endothelial cells using RNA sequencing. Liquid chromatography with MS/MS (LC/MSMS) and UV detection (LC/UV) was subsequently used to identify three key phytochemical compounds extracted from the mangosteen pericarp: α-Mangostin, γ-Mangostin, and Gartanin. Within the tested range of extraction temperatures by PHWE, our results demonstrated that an extraction temperature of 120 °C yielded the highest concentrations of α-Mangostin, γ-Mangostin, and Gartanin with a concomitant improvement in antioxidant capacity compared to other extraction temperatures. Using global transcriptomic profiling and bioinformatic analysis, the treatment of endothelial cells with mangosteen pericarp extracts (120 °C PHWE) for 48 h caused 408 genes to be differentially expressed. Furthermore, our results demonstrated that key biological processes related to "steroid biosynthesis and metabolism", likely involving the activation of the AMPK signaling pathway, were upregulated by mangosteen pericarp extract treatment. In conclusion, our study suggests a green extraction method to valorize phytochemical compounds from mangosteen pericarp as a natural product with potential beneficial effects on cardiometabolic health.